Highly efficient polyurethane ionomer corrosion inhibitor: The effect of chain structure - Banerjee S.; Mishra A.; Singh M.M.; Maiti B.; Ray B.; Maiti P. (My University, 2025)
A series of polyurethane (PU) ionomers with different degree of sulfonation (DS) have been synthesized and successfully used as corrosion inhibitor for mild steel (MS) in acidic medium. Nuclear magnetic resonance (NMR) and Fourier transform infra red (FTIR) spectra of the sulfonated PUs confirmed the sulfonation on the >NH group of the urethane linkage and DS increases with the increase in the ratio of the sulfonating agent and PU. More than 90% inhibition efficiency (IE) of sulfonated polyurethanes (SPU) has been reported using only 20 ppm of the ionomers. These ionomers inhibited the corrosion of MS through adsorption following the Langmuir adsorption isotherm. Surface coverage has been scaled using scanning electron microscopy (SEM) and atomic force microscopy (AFM). The effect of sulfonation on the electronic and chemical structure of PU molecules has also been investigated. Electronic structure calculations have been performed to predict the adsorption behavior of ionomers on the metal surface, and thereby, the relative inhibition has been quantitatively correlated with DS. © The Royal Society of Chemistry 2011.